2017
DOI: 10.1038/srep44921
|View full text |Cite
|
Sign up to set email alerts
|

Memory and synaptic plasticity are impaired by dysregulated hippocampal O-GlcNAcylation

Abstract: O-GlcNAcylated proteins are abundant in the brain and are associated with neuronal functions and neurodegenerative diseases. Although several studies have reported the effects of aberrant regulation of O-GlcNAcylation on brain function, the roles of O-GlcNAcylation in synaptic function remain unclear. To understand the effect of aberrant O-GlcNAcylation on the brain, we used Oga+/− mice which have an increased level of O-GlcNAcylation, and found that Oga+/− mice exhibited impaired spatial learning and memory. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
44
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 53 publications
2
44
2
Order By: Relevance
“…A previous study compared the effects of in five different groups: naïve, electroshock sleep-deprived and yoked-control, fish exposed to constant light (increasing wakefulness), and fish exposed to constant darkness (increasing sleep). 26 In addition, older mice with decreased memory function demonstrate chronically increased O-GlcNAcylation relative to young mice and elevated O-GlcNAcylation is suggested to contribute to L/M impairment. It has been reported that total SD for 72 consecutive hours interferes with learning performance in a spatial associative learning task in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study compared the effects of in five different groups: naïve, electroshock sleep-deprived and yoked-control, fish exposed to constant light (increasing wakefulness), and fish exposed to constant darkness (increasing sleep). 26 In addition, older mice with decreased memory function demonstrate chronically increased O-GlcNAcylation relative to young mice and elevated O-GlcNAcylation is suggested to contribute to L/M impairment. It has been reported that total SD for 72 consecutive hours interferes with learning performance in a spatial associative learning task in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to a decrease in sIPSC and mIPSC frequency in PrL layer II/III neurons, our group previously reported that mIPSC frequency remains unchanged in hippocampal CA1 neurons in Oga +/− mice 31 , indicating that the PrL layer II/III neurons are more sensitive to a decrease in OGA expression levels. This difference may result from the fact that the hippocampus is enriched with particularly high levels of OGT and OGA transcripts 44 , which may help to cope with the OGA heterozygosity.…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies demonstrated that both spatial learning and hippocampal synaptic plasticity are impaired in Oga +/− mice 31,32 , and that a deficit in O-GlcNAc cycling is associated with neurodegenerative and metabolic diseases 37,38 . The immediate donor molecule for O-GlcNAcylation, UDP-GlcNAc, is produced from glucose via the HBP, and thus, the degree of O-GlcNAc modification changes rapidly depending on blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations